1981
DOI: 10.1042/bj1940327
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent decay of cytochrome b5 and cytochrome b5 reductase in human erythrocytes

Abstract: Age-dependent decrease in cytochrome b5 was observed in erythrocytes from both a normal person and a patient with hereditary methaemoglobinaemia without neurological symptoms. With aging, concentrations of cytochrome b5 in erythrocytes from the patient were almost the same as those in the control. Age-dependent decrease in cytochrome b5 reductase activity in the control erythrocytes was also shown; however, the reductase activity was very low in erythrocytes from the patient over the whole age range. Our studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…As many other species, including zebrafish, are known to express CYB5, it seems likely that CYB5 and CYB5R may serve as the physiological reductants of Cygbs not only in humans but in many other species as well. Certainly CYB5 and CYB5R are important to mammalian Hb physiology as defects in both proteins are linked to methemoglobinemia. Nevertheless, it is also clear that the evolutionary pressure for Hb and Mb reduction is lower than for other putative globin substrates as these proteins have slow autoxidation rates (Table ). Some mammals do have very inefficient reducing systems for Hb; for instance, swine are particularly susceptible to methemoglobinemia due to their low concentrations of CYB5R in RBCs …”
Section: Discussionmentioning
confidence: 99%
“…As many other species, including zebrafish, are known to express CYB5, it seems likely that CYB5 and CYB5R may serve as the physiological reductants of Cygbs not only in humans but in many other species as well. Certainly CYB5 and CYB5R are important to mammalian Hb physiology as defects in both proteins are linked to methemoglobinemia. Nevertheless, it is also clear that the evolutionary pressure for Hb and Mb reduction is lower than for other putative globin substrates as these proteins have slow autoxidation rates (Table ). Some mammals do have very inefficient reducing systems for Hb; for instance, swine are particularly susceptible to methemoglobinemia due to their low concentrations of CYB5R in RBCs …”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the effect of aging and gender on the expression of membrane-bound b 5 and b 5 R. Previous study has shown that b 5 content and b 5 R activity decrease with aging in human erythrocytes (Matsuki et al, 1981). …”
Section: Introductionmentioning
confidence: 99%
“…O glóbulo vermelho, durante sua maturação, sofre uma diminuição no número de organelas citoplasmáticas (mitocôndrias, ribossomas) até a ausência total, perdendo, desta forma, a capacidade de repor as enzimas utilizadas para a redução da metemoglobina, formada' quando da ação oxidante exercida pela sulfona. Isto é demonstrado em publicação de autores que encontraram menor atividade enzimática nos eritrócitos mais velhos de pessoas normais e nos pacientes portadores de deficiência da NADH-citocromo-b5-redutase 30 .…”
Section: Resultsunclassified